2006
DOI: 10.1039/b600010j
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the bathochromically shifted optical spectra of meso-tetrathien-2′- and 3′-ylporphyrins as compared to meso-tetraphenylporphyrin

Abstract: The UV-Vis and fluorescence spectra of free base and diprotonated meso-tetrathien-2'-ylporphyrins are, when compared to the spectra of meso-tetra-phenyl- or even -thien-3'-ylporphyrins, characterized by surprisingly large red-shifts. A comparison of the optical spectra and the computed rotational barriers for these meso-aryl-substituted porphyrins and a detailed conformational analysis of the single crystal X-ray structure of a diprotonated meso-tetrathien-2'-ylporphyrin suggest that the origin of the altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 51 publications
4
64
2
Order By: Relevance
“…This parallels the findings for the loss of the first imidazole from the octahedral complexes. It is well established that thienyl groups play a much stronger role in the electronic structure of the porphyrin than the phenyl rings [36]. Our gas-phase findings, in fact, correlate well with the solution data.…”
Section: Relative Binding Strength Of the Axialsupporting
confidence: 79%
See 3 more Smart Citations
“…This parallels the findings for the loss of the first imidazole from the octahedral complexes. It is well established that thienyl groups play a much stronger role in the electronic structure of the porphyrin than the phenyl rings [36]. Our gas-phase findings, in fact, correlate well with the solution data.…”
Section: Relative Binding Strength Of the Axialsupporting
confidence: 79%
“…It is possible that this particular distinction arises from the presence of multiple conformations of the thienyl substituents in the gas phase experiments that are not reflected in the computations. It has been shown that such issues affect the photophysics of free [11] and [12] [36].…”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alas, we would caution against translating this result to porphyrinoid pigments for which a large coplanarity of the meso-aryl substituents is known to take place, and for which a larger electronic influence of the aryl groups has to be assumed. [46,47] 4. Experimental…”
Section: Discussionmentioning
confidence: 99%